Electron-rotation coupling in diatomics under strong-field excitation - Liu, Yan Rong; Wu, Yong; Wang, Jian Guo; Vendrell, Oriol; Kimberg, Victor; Zhang, Song Bin (Physical review, 2020)
The photoexcitation and photodissociation of diatomic molecules by intense pulse lasers has been the subject of extensive investigations over the past decades. However, the usually employed theoretical framework neglects the coupling between the molecular rotational angular momentum (R) and the angular momentum of the electrons projected onto the molecular axis Omega = Lambda + Sigma, which results in the known Lambda-doubling phenomenon in high-resolution electronic spectra of diatomic molecules. While neglecting this coupling is an excellent approximation in the weak-field or perturbative regime owing to the large mass difference between the rotating atoms and the electrons, the approximation breaks down for intense laser pulses because of the repeated Rabi cycling of the electronic transitions, which can have a significant effect on the rotational degrees of freedom of the molecule. By correcting the transition dipole matrix elements and introducing angular basis sets based on Wigner D functions, the conventional theoretical treatment is generalized to a universal description valid for both the weak- and strong-field regimes. The theoretical treatment developed here is applied to the vertical bar(1)Sigma > to vertical bar(1)Pi > transitions in diatomic systems. Our results reveal that, for field intensities resulting in about one Rabi cycling for extreme ultraviolet or x-ray transitions, the theoretical predictions by the conventional theoretical frame need to be corrected when considering observables such as the molecular alignment and the angular distribution of the photofragments.